Anisotropy in ultrasound shear wave elastography: An add-on to muscles characterization - Ngo, Ha-Hien-Phuong; Poulard, Thomas; Brum, Javier; Gennisson, Jean- Luc (Frontiers in Physiology, 2022)
Ultrasound shear wave elastography was developed the past decade, bringing new stiffness biomarker in clinical practice. This biomarker reveals to be of primarily importance for the diagnosis of breast cancer or liver fibrosis. In muscle this biomarker become much more complex due to the nature of the muscle itself: an anisotropic medium. In this manuscript we depict the underlying theory of propagating waves in such anisotropic medium. Then we present the available methods that can consider and quantify this parameter. Advantages and drawbacks are discussed to open the way to imagine new methods that can free this biomarker in a daily clinical practice.